Development and reliability and validity test of the sleep health literacy scale for college students - ZhengDa Long; LiPing Huang (BMC Public Health)
Abstract Purpose It is evident that there are some discrepancies in the connotations and substance of sleep health literacy and health literacy. The latter encompasses a broader construct, including health-related knowledge and the capacity for decision-making in domains such as diet, exercise, mental well-being and disease prevention. In contrast, sleep health literacy is a more specialised domain that aims to assist individuals in optimising their sleep quality and modifying their sleep behaviour.Sleep health literacy is defined as a specialized extension of general health literacy, with a specific focus on sleep-related knowledge and behaviors. Sleep health literacy is defined as the ability of an individual to obtain, understand, analyse and apply basic sleep health information or services and to make correct sleep health decisions.However, no formal assessment tool for sleep health literacy has been developed to date. Therefore, the Sleep Health Literacy Scale for College Students (SHLS-ST) was developed and its reliability was tested. Methods The present study is founded upon extant theoretical frameworks and scales, in addition to comprehensive literary research, group interviews, and the Delphi expert consultation method. We administered questionnaires to on 300 college students, and the survey data were used for item analysis, exploratory factor analysis, confirmatory factor analysis, convergent validity, discriminant validity, and correlation analysis. These analyses were used to test the structural validity and reliability of the SHLS-ST. Results The Sleep Health Literacy Scale for College Students was developed with 26 items. Exploratory factor analysis yielded five common factors, with a cumulative variance contribution of 72.05%, and Pearson’s correlation coefficients between the five factor scores and the total scale score ranging from 0.568 to 0.947. The overall Cronbach’s α coefficient of the scale was 0.960, the overall split-half reliability of the scale was 0.922, and the reliability coefficient of the test-retest reliability of 77 college students after an interval of half a month was 0.974. Conclusion The Sleep Health Literacy Scale for College Students has a good reliability and validity, and is suitable for the assessment of college students’ sleep health literacy. However, the length of the scale may affect its usability and participants’ engagement in the assessment process.